Thermomechanical model for solidification and cooling simulation of Ni-based superalloy components. (1st March 2021) - Labergère, C.; Long, M.; Badreddine, H.; Niane, N-T.; Grange, D.; Saanouni, K.
Abstract: One of the challenges encountered in the industrialization of new single-crystal superalloys parts (like high-pressure turbine blades and vanes for aircraft engines) is to limit the mechanical stresses during the solidification and cooling of the metal. In order to accurately predict the viscoplastic flow as well as the thermo-mechanical behaviour of Ni-based superalloy during its cooling, in this study a thermodynamically-consistent thermo-elasto-viscoplastic model was developed. This model takes into account the solid-liquid transition occurring in the material during the cooling phase. This is done by introducing a compressible-type viscoplastic yield function based on appropriate equivalent stress depending on volume fraction of the solid phase formed by the propagation of dendrites inside the liquid phase of the material. This model was implemented in Abaqus/Standard© F.E. code and applied to the identification of material parameters of Ni-based superalloy using isothermal tensile-relaxation tests driven for different strain rates and temperatures. First, anisothermal tensile-compression test was simulated on a single integration point. A comparison of the experimental and numerical stress-strain response partially validate the model. Second, a benchmark test involving casting of a rectangular Ni-based superalloy bar in a sand mold was simulated and analyzed.